Влияние нитрозометилмочевины на изменчивость Phalaris canariensis - Кудина, Г.А.; Червинский, А.Ю. (Промышленная ботаника, 2003)
The results of the studies of the effect of NMC on the seeds of the ornamental Canary grass are given. The inhibition of seeds , germination, increase of the energy of germination, decrease of the viability of seedlings and a lower quality of seeds of the trial plants were indicated. 0,005% NMC, the exposition of which was 8 hours stimulated the growth of plants, the concentration of which was 0,01%, during 8 hours, caused the inhibiting effect on the development of plants and their reproductive function. The forms with the good prospects as for the further selection were defined among the trial plants.